2014
DOI: 10.1111/jcpe.12281
|View full text |Cite
|
Sign up to set email alerts
|

Association between periodontitis and preeclampsia in never‐smokers: a prospective study

Abstract: There was a significant relationship between periodontitis and the occurrence of preeclampsia among never-smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 41 publications
0
26
0
3
Order By: Relevance
“…Xiong et al (2009) found that periodontitis was associated with GDM (77.4% of pregnant women with GDM had periodontis) with an adjusted odds ratio of 2.6 and a confidence interval of 95% in their case-control study of 53 pregnant women with GDM and 106 without GDM. Ha et al (2014) found "a significant relationship between periodontitis and preeclampsia in never smokers" (p. 869) in their prospective cohort study of 283 pregnant women who had never smoked, 67 with periodontitis and 216 without periodontitis.…”
Section: Periodontitismentioning
confidence: 95%
See 1 more Smart Citation
“…Xiong et al (2009) found that periodontitis was associated with GDM (77.4% of pregnant women with GDM had periodontis) with an adjusted odds ratio of 2.6 and a confidence interval of 95% in their case-control study of 53 pregnant women with GDM and 106 without GDM. Ha et al (2014) found "a significant relationship between periodontitis and preeclampsia in never smokers" (p. 869) in their prospective cohort study of 283 pregnant women who had never smoked, 67 with periodontitis and 216 without periodontitis.…”
Section: Periodontitismentioning
confidence: 95%
“…Recent studies have shown an association between periodontitis during pregnancy and low birth weight (LBW), very low birth weight (VLBW), preeclampsia, and GDM (Corbella et al, 2016;Guimarã es et al, 2012;Ha, Jun, Ko, Paik, & Bae, 2014;Xiong et al, 2009). Guimarã es et al (2012 showed in their crosssectional study of 1,206 postpartum women that "maternal periodontitis was associated with a decrease in mean birth weight, as well as LBW and VLBW" (p. 1024).…”
Section: Periodontitismentioning
confidence: 98%
“…Periodontitis is related to rheumatoid arthritis, and treatment for the former has an effect on both the latter and systemic inflammation (Payne et al, 2015). In addition, preeclampsia (Ha et al, 2014), other complications during pregnancy (Zi et al, 2015), and inflammatory bowel disease (Vavricka et al, 2013), amongst other conditions, have been shown to be associated with chronic periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, the authors reported that Pg lipopolysaccharide suppressed trophoblastic invasion in the presence of nicotine, 33 and results are consistent with pregnancy complications that are common among smokers. However, a recent report suggested that periodontitis is an independent risk factor for PE in non‐smoking women 34 . Although early studies suggested the presence of Pg in placental tissues 35,36 and demonstrated in vitro infection in cultured trophoblasts, 37 its pathologic role is not clear.…”
mentioning
confidence: 99%